(untitled) (Italian Journal of Public Health, 2009)
Background: Research provides the important evidence base for public health practice. We sought to compare the current support for public health research within European countries. Methods: Within a collaborative study SPHERE (Strengthening Public Health Research in Europe), we developed an e-mail questionnaire and sent it to 93 representatives of national member associations of the European Public Health Association. We compared the answers with reference to tree macro-areas: Northern, Southern and Eastern Europe. Results: We gained responses for 22 of the 39 European countries (56% country response rate). Current priorities at national level were: health service and patient safety for Northern Europe; infectious disease, health service and cardiovascular disease for Southern Europe; and food safety and nutrition, environmental and occupational health for Eastern Europe. Respondents gave fewer priorities for international research. In Northern Europe the priorities empathized were health promotion, prevention and education (26.3%) together the injuries and alcohol habits (26.3%); health economics, health impact assessment, evaluations of services and programmes in Southern and Eastern Europe respectively 30% and 41.7%. Conclusions: Support for public-health research differs across Europe, and barriers to undertaking better research included structures and sufficient personnel. National public health associations and public authorities should cooperate in order to find effective answers to common problems